The Effects Of Endorser Credibility, Attitude Toward To ADS, And Brand Attitude On Purchase Intention - Didit Darmawan; Rahayu Mardikaningsih; Mila Hariani (STIE Mandala Jember, 2019)
Development of motorcycle industry in Indonesian was represent by four producer’ from Japan, such Honda, Suzuki, Yamaha, and Kawasaki. Each brand was known by society, but how would people perceived it. How celebrity endorsements affect consumer purchase decisions is studied extensively by marketing and social psychology researchers. This research will measure endorser credibility of one of motorcycle brand. This research also conducts to discuss the impact of endorser credibility on attitude toward to ad and also the impact of attitude toward to ad and brand attitude on consumers’ purchase intention. Researcher used path analysis with the AMOS program to calculate the effect of each variable to consumers’ purchase intention. It’s suggested that brand attitude would greater impact on consumers’ purchase intention compare to rather than attitude toward to ad. A model will be developed to describe these relationships.